MODEL PENGEMBANGAN SUMBER AIR BAKU: PENDEKATAN REKAYASA DAN EKONOMI-MANAJEMEN - FARIED WIJAYA MANSOER (UGM, 1999)
The fulfillment of domestic water in particular region requires planning that depends on the potential availability of water and the future growth rate of the region. The rapid growth rate of various recently experienced by Indonesia will result in a greater demand for domestic water. Considering the information above, therefor, domestic water availability system must be under continous surveilance.